2015
DOI: 10.1073/pnas.1413451112
|View full text |Cite
|
Sign up to set email alerts
|

SWI/SNF chromatin remodeling regulates alcohol response behaviors in Caenorhabditis elegans and is associated with alcohol dependence in humans

Abstract: Alcohol abuse is a widespread and serious problem. Understanding the factors that influence the likelihood of abuse is important for the development of effective therapies. There are both genetic and environmental influences on the development of abuse, but it has been difficult to identify specific liability factors, in part because of both the complex genetic architecture of liability and the influences of environmental stimuli on the expression of that genetic liability. Epigenetic modification of gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 52 publications
2
57
0
Order By: Relevance
“…This chromatin remodeling causes a reduction in expression of NPY in the amygdala which fits with enhanced anxiety during alcohol withdrawal (Pandey et al, 2008). In addition, the SWI/SWF chromatin remodeling complex is required in adult neurons of C.elegans for acute alcohol tolerance and genetic variation in a member of this complex is associated with alcohol dependence in humans (Mathies et al, 2015). Interestingly, a recent study demonstrated that the sigma-1 receptor mediates cocaine-induced transcriptional regulation by recruiting chromatin-remodeling factors at the nuclear envelope, suppressing the expression of monoamine oxide B (MAOB) in the nucleus accumbens (Tsai et al, 2015).…”
Section: Genome-wide Association Studies Of Alcohol Dependencementioning
confidence: 99%
“…This chromatin remodeling causes a reduction in expression of NPY in the amygdala which fits with enhanced anxiety during alcohol withdrawal (Pandey et al, 2008). In addition, the SWI/SWF chromatin remodeling complex is required in adult neurons of C.elegans for acute alcohol tolerance and genetic variation in a member of this complex is associated with alcohol dependence in humans (Mathies et al, 2015). Interestingly, a recent study demonstrated that the sigma-1 receptor mediates cocaine-induced transcriptional regulation by recruiting chromatin-remodeling factors at the nuclear envelope, suppressing the expression of monoamine oxide B (MAOB) in the nucleus accumbens (Tsai et al, 2015).…”
Section: Genome-wide Association Studies Of Alcohol Dependencementioning
confidence: 99%
“…Interestingly, at least two genes ( swsn-7 and swsn-9 ) coding for SWI/SNF complex members in worms are required for the proper development of functional alcohol tolerance (Mathies et al, 2015). Furthermore, variants in one human SWI/SNF complex gene ( BRD7 ) associated significantly with alcohol dependence in a human genomewide association study (Mathies et al, 2015). Our results suggest that JmjC-KDMs might participate in the regulation of alcohol behaviors by modulating transcription via the SWI/SNF complex.…”
Section: Discussionmentioning
confidence: 99%
“…We found that PBAF functions in differentiated neurons for the development of AFT (Mathies et al, 2015). Importantly, variation in two human SWI/SNF complex genes, SMARCA2 and BRD7 , was associated with AD in the Irish Affected Sib Pair Study for Alcohol Dependence (IASPSAD) (Mathies et al, 2015). …”
Section: Introductionmentioning
confidence: 87%
“…We previously found that BAF and PBAF affect different components of the acute response to ethanol in the genetic model Caenorhabditis elegans (Mathies et al, 2015): BAF is required for normal initial sensitivity to ethanol, while PBAF is required for the development of acute functional tolerance to ethanol (AFT). We found that PBAF functions in differentiated neurons for the development of AFT (Mathies et al, 2015). Importantly, variation in two human SWI/SNF complex genes, SMARCA2 and BRD7 , was associated with AD in the Irish Affected Sib Pair Study for Alcohol Dependence (IASPSAD) (Mathies et al, 2015).…”
Section: Introductionmentioning
confidence: 99%